A inclusão educacional e educação superior: realidade e perspectivas na educação a distância - Lorensi, Vanise Mello (2014)
This research is part of the Research Line Special Education of Postgraduate in Education Program from Universidade Federal de Santa Maria. This present study considered as objectives: analyzing how the Undergraduate Course of Special Education in the modality Distance Education from Universidade Federal de Santa Maria enables inclusive actions to its students with disabilities. We took as a reference this Course because it is pioneer in distance education (Educação a distância EaD) in this institution and because it has students with disabilities included. We elected as theoretical approach the works of Vygotsky (1997, 2007, 2009, 2010) which bases the conceptions about learning and development of the individual from his historical and social interactions. Authors such as Corradi (2011); Dias (2003); Santarosa (2003, 2010, 2012); Sassaki (2005); Sonza (2008) who bring theoretical basis to the questions of assistive technology, communication technologies and available information and accessibility to the learning virtual environment. We chose to work with the research with a qualitative approach (GIL, 2009), a case study, with the authors (GIL, 1991; LUDKE, ANDRÉ, 1986) through face-to-face interviews or virtual interviews with participants of the Course. The content analysis (BARDIN, 2008) was the technique elected to interpret the data and it allowed the achievement of the following results: EaD can be inclusive to any student, with disability or not; EaD can be favored by the use of information and communication technologies and to the students with disability to the technologies that are accessible to the computer; the educational inclusion in higher education is still a challenge in relation to formal and distance Education (EaD); the inclusion to students with disabilities in the Undergraduate Course of Special Education in the modality Distance Education from UFSM still demands resources and specific services of accessibility; the accessibility issues are being planned/organized according to the necessities of the demands from the students that start the Course; EaD was considered by the individual with disabilities that is included as a viable option to fullfil the dream of academic formation in the higher education level, because of the flexibility of space/time. From what was exposed and considering the preview objectives and the achieved results, the conclusions that can be found in the body of the text, point to some indicators, recommendations and perspectives to an inclusive education proposal in the distance education scope.